2007
DOI: 10.1101/gr.6073107
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a genome-scale structural map at single-nucleotide resolution

Abstract: Few methods are available for mapping the local structure of DNA throughout a genome. The hydroxyl radical cleavage pattern is a measure of the local variation in solvent-accessible surface area of duplex DNA, and thus provides information on the local shape and structure of DNA. We report the construction of a relational database, ORChID (OH Radical Cleavage Intensity Database), that contains extensive hydroxyl radical cleavage data produced from two DNA libraries. We have used the ORChID database to develop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 43 publications
1
81
0
2
Order By: Relevance
“…They were, however, significantly enriched in Lamin B1 associated domains (LADs), in gene-poor Giemsa positive, strongly A/Trich heterochromatin, in solvent-accessible sites (BU ORChID), and at methylated cytosines ( Fig. 4; Supplemental Table S9; Balasubramanian et al 1998;Greenbaum et al 2007;Guelen et al 2008;Meissner et al 2008). In contrast, they were significantly depleted in regions with histone methylation/acetylation associated with active gene transcription, especially in regions with high H3K36me3 levels, associated with transcriptional activation and elongation (Ram et al 2011) and at conserved loci (GERP) (Supplemental Fig.…”
Section: Spectrum Of Functional Elements Of Somatic Mutations Is Simimentioning
confidence: 99%
“…They were, however, significantly enriched in Lamin B1 associated domains (LADs), in gene-poor Giemsa positive, strongly A/Trich heterochromatin, in solvent-accessible sites (BU ORChID), and at methylated cytosines ( Fig. 4; Supplemental Table S9; Balasubramanian et al 1998;Greenbaum et al 2007;Guelen et al 2008;Meissner et al 2008). In contrast, they were significantly depleted in regions with histone methylation/acetylation associated with active gene transcription, especially in regions with high H3K36me3 levels, associated with transcriptional activation and elongation (Ram et al 2011) and at conserved loci (GERP) (Supplemental Fig.…”
Section: Spectrum Of Functional Elements Of Somatic Mutations Is Simimentioning
confidence: 99%
“…For the purpose of the work presented here, a key feature of the hydroxyl radical cleavage experiment is that different DNA sequences can produce similar cleavage patterns (Price and Tullius 1993;Greenbaum et al 2007). Since the same local DNA structure can be adopted by different sequences of nucleotides, it is possible that a region of the genome that functions by virtue of its structure may not be conserved in nucleotide sequence.…”
Section: Resultsmentioning
confidence: 99%
“…We have determined the hydroxyl radical cleavage patterns of a substantial collection of DNA sequences, constructed a database of these patterns, and then used this database to develop an algorithm to predict the cleavage pattern of any DNA sequence (Greenbaum et al 2007;see Methods). We used this algorithm to predict the cleavage pattern of the 30 Mb of DNA within the ENCODE regions.…”
Section: Resultsmentioning
confidence: 99%
“…The question that is often raised is whether these short lengths of DNA may in fact not be relevant (and, in the case of crystals, be otherwise distorted (Dickerson et al, 1994)) relative to sequences embedded in a genomic context. Studies by Tullius' group using hydroxyl-radical foot printing (Greenbaum et al, 2007), have shown significant sequence dependent variation in the solvent accessibility and, thus, the helical structure of protein-free genomic DNA. These structural variations at the genomic level are highly correlated with variations in helical parameters measured in DNA crystal structures (unpublished results) derived from a selfconsistent data set (Hays et al, 2005).…”
Section: B-dnamentioning
confidence: 99%